2021
DOI: 10.3390/ijns7020028
|View full text |Cite
|
Sign up to set email alerts
|

Low Psychosine in Krabbe Disease with Onset in Late Infancy: A Case Report

Abstract: Krabbe disease (KD) is a rare inherited neurodegenerative disorder caused by a deficiency in galactocerebrosidase enzyme activity, which can present in early infancy, requiring an urgent referral for hematopoietic stem cell transplantation, or later in life. Newborn screening (NBS) for KD requires identification and risk-stratification of patients based on laboratory values to predict disease onset in early infancy or later in life. The biomarker psychosine plays a key role in NBS algorithms to ascertain proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Although the screening strategy included in the nomination of KD to the RUSP had been recommended in previous publications [12,13], discussion among the authors identified several reasons for the lack of adoption by all NBS programs. One is the difficulty of state programs to adjust existing screening algorithms due to the concern, only supported by anecdotal reports [24], of possibly missing patients with IKD or even an AKD case following a change that focuses on IKD and LIKD as the primary targets of screening. Several programs rely on their advisory committees to determine screening algorithms, some even to set cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the screening strategy included in the nomination of KD to the RUSP had been recommended in previous publications [12,13], discussion among the authors identified several reasons for the lack of adoption by all NBS programs. One is the difficulty of state programs to adjust existing screening algorithms due to the concern, only supported by anecdotal reports [24], of possibly missing patients with IKD or even an AKD case following a change that focuses on IKD and LIKD as the primary targets of screening. Several programs rely on their advisory committees to determine screening algorithms, some even to set cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Galactosylsphingosine, also known as psychosine, is a wellknown biomarker for early-onset form and its measurement in dried blood spots is improving the newborn screening programs for KD; nevertheless, lower or normal values of psychosine may be present in late-onset phenotype [10,11]. In our patients, we determined the levels of HexSph (galactosylsphingosine + glucosylsphingosine) by liquid chromatography coupled with tandem mass spectrometry, a validate method for simultaneous quantification of several lysosphingolipids [12].…”
Section: Discussionmentioning
confidence: 99%
“…11 A patient who developed KD in late infancy had a pathogenic genotype, showed reduced enzyme activity but surprisingly low psychosine levels, suggesting that measuring psychosine levels should be combined with other measurements, such as enzyme levels, as well as genotyping and correlation with the patient's clinical presentations. 40 Therefore, magnetic resonance (MR) images showing abnormal signals, as well as the presence of globoid cells must be done before final diagnosis of the disease. 41 For instance, MR imaging diagnosed A 32-year-old woman with headache as adult onset KB with two pathogenic variants in GALC.…”
Section: Clinical Observationsmentioning
confidence: 99%